Hegel’s Ethics - Hajj Muhammad Legenhausen (Religious Inquiries, 2012)
My purpose in this article is not to offer any original insights into Hegel’s ethics, but merely to provide a brief overview that draws upon the most reliable secondary sources. In order to help organize the material, I compare Hegel’s views with the communitarian critique of liberalism. Following this, there is a brief account of the relation between Hegel’s ethical and religious thought. Hegel’s philosophy is one of reconciliation. He is both a follower of Kant and a sharp critic of Kant. With Kant, he affirms the idea of moral autonomy, that moral agency requires us to think for ourselves and impose moral obligations upon ourselves. Unlike Kant (at least as usually interpreted), however, he does not think that this means that the only motivation for moral behavior should be the will to do one’s duty. Because of the antinomy of free will and determinism, Kant concluded that agency springs from a noumenal realm beyond the phenomenal world. Hegel seeks to reconcile freedom with causal constraints in a form of compatibalism that differs fundamentally from the soft determinism of the empiricist tradition. Kant argued that morality must derive from reason. Hegel agrees, but he understands reason as a process in which the finite self overcomes itself through its identification with others. My indebtedness to Robert Wallace’s recent book on this topic will be obvious; my gratitude to him should be, as well